Plays in American Periodicals, 1890–1918 - Smith, Susan Harris. author. aut Link
XIX, 224 p.
Keywords: This book examines over 125 American, English, Irish and Anglo-Indian plays by 70 dramatists which were published in 14 American general interest periodicals aimed at the middle-class reader and consumer.